Pengaruh Praktik Manajemen Keuangan dan Pengendalian Internal Terhadap Akuntabilitas Organisasi Ikatan Motor Indonesia (IMI) Sumatera Barat - Atika Atika; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to analyze the influence of financial management practices and internal control on organizational accountability in provincial-level non-profit sports organizations that manage significant funds. This study was conducted due to the limited empirical evidence regarding accountability mechanisms in regional sports organizations, which have different structures and management patterns than public or corporate organizations. Data were collected through questionnaires from active administrators and analyzed using validity and reliability tests, classical assumption checks, and multiple linear regression. The novelty of this study lies in its focus on provincial sports organizations and the role of financial management practices as a primary factor in accountability, differing from previous studies that focused on the public sector or corporations. The results indicate that financial management practices have a positive and significant effect on accountability, while internal control does not have a direct effect when analyzed in conjunction with financial management. These findings emphasize the importance of systematic budget planning, transparent recording and reporting, and effective financial oversight to enhance accountability. The study concludes that financial management practices are key to improving accountability and recommends that future research use a longitudinal design, involve other organizations, and consider additional variables such as leadership and organizational culture.